1200MPa-grade hot-rolled galvanized martensitic steel and preparation method thereof

By rationally designing the chemical composition and preparation process of the steel, and using Cu, Nb and Ti composite reinforcement, the problem of low strength of existing hot-rolled galvanized martensite steel is solved, and tensile strength and high yield strength of 1200MPa grade are achieved, and flange and hole reaming performance is improved.

CN119824322APending Publication Date: 2025-04-15SHOUGANG GROUP CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510118695.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing hot-rolled galvanized martensitic steel has low strength and is difficult to meet the high-strength needs.

Method used

By rationally designing the chemical composition of the steel, using Cu-Nb and Ti composite reinforcement, Cu-rich phase, NbC, TiC or (Nb, Ti)C, etc., to improve the strength of the steel. The preparation method includes heating, rough rolling, descaling, finishing rolling, cooling after rolling, coiling, pickling and continuous annealing and galvanizing.

Benefits of technology

The tensile strength and high yield strength of 1200MPa grade are achieved, which improves flange and reaming performance and reduces alloy cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824322A_ABST
    Figure CN119824322A_ABST
Patent Text Reader

Abstract

The invention provides 1200MPa-grade hot-rolled galvanized martensitic steel and a preparation method thereof, and belongs to the field of steel preparation. The hot-rolled galvanized martensitic steel comprises a steel matrix and a galvanized layer attached to at least part of the surface of the steel matrix, and the steel matrix comprises the following chemical components in percentage by mass: 0.1%-0.25% of C, 0.1%-0.5% of Si, 1.5%-2.5% of Mn, 0-0.01% of P, 0-0.003% of S, 0.01%-0.3% of Al, 0.05%-0.5% of Cu, 0.02%-0.2% of Ni, 0-0.05% of Nb, 0.02%-0.1% of Ti, 0.001%-0.003% of B and the balance of Fe and inevitable impurities. The chemical components of the steel are reasonably designed, so that the problem of low strength of hot-rolled galvanized martensitic steel in the prior art is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of steel preparation, and in particular to a 1200MPa grade hot-rolled galvanized martensitic steel and a preparation method thereof. Background Art

[0002] Martensitic steel has a high yield-to-strength ratio, high tensile strength and good flanging and hole expansion performance. It is one of the advanced high-strength steels with the greatest lightweight potential and is widely used in the manufacture of sill beams, door anti-collision bars and truck compartment panels.

[0003] However, the production of cold-rolled martensitic steel often requires high annealing temperatures and high cooling rates to achieve austenitization and promote martensitic phase transformation, which places extremely high demands on equipment capacity. For units that do not have water quenching or high-hydrogen rapid cooling capabilities, the only way to improve hardenability is by adding a large amount of alloying elements, which increases alloy costs. Compared with cold-rolled martensitic steel, the production of hot-rolled martensitic steel is easy to operate and economical, but the hot-rolled martensitic steel currently widely used generally has low strength. With the continuous development of "replacing cold with heat" and the continuous improvement of automobile companies' requirements for the quality of raw materials, the demand for high-strength hot-rolled martensitic steel continues to increase. Summary of the invention

[0004] The present application provides a 1200MPa grade hot-rolled galvanized martensitic steel and a preparation method thereof, so as to solve the technical problem of low strength of existing hot-rolled galvanized martensitic steel.

[0005] In the first aspect, the present application provides a 1200MPa grade hot-rolled galvanized martensitic steel, which includes a steel substrate and a galvanized layer attached to at least a portion of the surface of the steel substrate. The chemical composition of the steel substrate includes, by mass fraction: C: 0.1% to 0.25%, Si: 0.1% to 0.5%, Mn: 1.5% to 2.5%, P: 0 to 0.01%, S: 0 to 0.003%, Al: 0.01% to 0.3%, Cu: 0.05% to 0.5%, Ni: 0.02% to 0.2%, Nb: 0 to 0.05%, Ti: 0.02% to 0.1%, B: 0.001% to 0.003%, and the remainder is Fe and unavoidable impurities.

[0006] Optionally, the microstructure of the steel matrix includes, by area ratio, tempered martensite: 90% to 99%, and other structures: 1% to 10%, wherein the other structures include one or more of ferrite, bainite and residual austenite.

[0007] Optionally, a precipitate phase is distributed on the matrix of the tempered martensite, and the precipitate phase includes one or more of a Cu-rich phase, NbC, TiC and (Nb, Ti)C.

[0008] Optionally, the steel substrate satisfies at least one of the following properties: yield strength ≥ 950 MPa, tensile strength ≥ 1200 MPa, elongation after fracture ≥ 11%, hole expansion rate ≥ 70%, 180° ultimate cold bending radius r ≤ 1.5a, where a is the thickness of the steel substrate.

[0009] In a second aspect, the present application provides a method for preparing the 1200 MPa grade hot-rolled galvanized martensitic steel according to any one of the embodiments in the first aspect, and the method includes:

[0010] Obtaining a slab having the chemical composition;

[0011] Heating, rough rolling, finish descaling, finish rolling, post-rolling cooling, and coiling the slab to obtain a hot-rolled coil;

[0012] Performing surface treatment on the hot-rolled coil to obtain a pickled sheet; and

[0013] Performing continuous annealing and galvanizing on the pickled sheet, and then cooling to room temperature to obtain a hot-rolled galvanized martensitic steel.

[0014] Optionally, the relationship between the thickness of the hot-rolled coil and the pressure of the finish descaling is as follows:

[0015] When the thickness of the hot-rolled coil is 1.8 mm ≤ d ≤ 2.5 mm, the pressure of the finish descaling is 21 MPa to 24 MPa, where d is the thickness of the hot-rolled coil;

[0016] When the thickness of the hot-rolled coil is 2.5 mm < d ≤ 3.5 mm, the pressure of the finish descaling is 24 MPa to 27 MPa, where d is the thickness of the hot-rolled coil;

[0017] When the thickness of the hot-rolled coil is 3.5 mm < d ≤ 6.0 mm, the pressure of the finish descaling is 27 MPa to 30 MPa, where d is the thickness of the hot-rolled coil.

[0018] Optionally, the instantaneous minimum cooling rate of the post-rolling cooling ≥ 25 °C / s, and the average cooling rate ≥ 30 °C / s; the relationship between the thickness of the hot-rolled coil and the cooling method of the post-rolling cooling is as follows:

[0019] When the thickness of the hot-rolled coil is 1.8 mm ≤ d ≤ 3.5 mm, the post-rolling cooling adopts laminar flow water cooling, where d is the thickness of the hot-rolled coil;

[0020] When the thickness of the hot-rolled coil is 3.5 mm < d ≤ 6.0 mm, the post-rolling cooling adopts a combined water cooling of ultra-fast cooling and laminar flow water cooling, where d is the thickness of the hot-rolled coil.

[0021] Optionally, the heating temperature is 1240° C. to 1270° C., and the soaking time is 30 min to 50 min; and / or,

[0022] The end temperature of the rough rolling is 1070°C to 1140°C; and / or,

[0023] The inlet temperature of the finishing rolling is 1000°C to 1050°C, and the final rolling temperature is 860°C to 900°C; and / or,

[0024] The coiling temperature is 300°C to 400°C.

[0025] Optionally, the surface treatment includes: scale breaking and straightening and continuous pickling, the elongation of the scale breaking and straightening is 0.3% to 0.5%; the strip running speed of the continuous pickling is 80m / min to 180m / min, and the free acid concentration of the pickling tank is 20g / L to 30g / L.

[0026] Optionally, the pickled plate is subjected to continuous annealing and galvanizing, and then cooled to room temperature to obtain hot-rolled galvanized martensitic steel, comprising:

[0027] Preheating the pickling plate to 210°C to 230°C;

[0028] The preheated pickling plate is heated to 600°C to 660°C at a rate of 5°C / s to 25°C / s;

[0029] Keeping the heated pickled plate warm for 30s to 80s;

[0030] The pickled plate after heat preservation is rapidly cooled to 420°C to 440°C at a rate of 5°C / s to 15°C / s;

[0031] The pickled steel sheet after rapid cooling is galvanized, and the thickness of the galvanized layer is controlled to be 7 μm to 20 μm, so as to obtain a galvanized steel sheet;

[0032] Cooling the galvanized steel sheet to 220° C. to 250° C.;

[0033] The cooled galvanized steel sheet is subjected to skin-pass treatment, and the skin-pass rolling force is controlled to be 1500 kN to 2500 kN, and then cooled to room temperature to obtain hot-rolled galvanized martensitic steel.

[0034] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0035] The present application provides a 1200MPa grade hot-rolled galvanized martensitic steel, which rationally designs the chemical composition of the steel, and adopts Cu, Nb, and Ti composite strengthening to precipitate Cu-rich phase, NbC, TiC, or (Nb, Ti) C, etc., to improve the strength of the steel. The yield strength of the obtained martensitic steel is ≥950MPa, the tensile strength is ≥1200MPa, the elongation after fracture is ≥11%, the hole expansion rate is ≥70%, and the 180° limit cold bending radius r≤1.5a. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0037] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0038] Figure 1 A schematic flow chart of a method for preparing a 1200MPa grade hot-rolled galvanized martensitic steel provided in an embodiment of the present application;

[0039] Figure 2 The microstructure of a 1200MPa grade hot-rolled galvanized martensitic steel provided in Example 1 of the present application. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0041] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0042] In addition, in the description of the specification of the present application, the terms "including", "comprising", etc. mean "including but not limited to". In this article, relational terms such as "first" and "second", etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A and B can be singular or plural. In this article, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of singular or plural items. For example, "at least one of a, b, or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e. a and b), ac, bc or abc, where a, b, c can be single or plural, respectively.

[0043] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0044] The present application provides a 1200MPa grade hot-rolled galvanized martensitic steel, which comprises a steel substrate and a galvanized layer attached to at least a portion of the surface of the steel substrate. The chemical composition of the steel substrate comprises, by mass fraction, C: 0.1% to 0.25%, Si: 0.1% to 0.5%, Mn: 1.5% to 2.5%, P: 0 to 0.01%, S: 0 to 0.003%, Al: 0.01% to 0.3%, Cu: 0.05% to 0.5%, Ni: 0.02% to 0.2%, Nb: 0 to 0.05%, Ti: 0.02% to 0.1%, B: 0.001% to 0.003%, and the remainder is Fe and unavoidable impurities.

[0045] In the embodiment of the present application, the positive effect of controlling the C content to 0.1% to 0.25% is that C has the effect of improving hardenability and can inhibit the ferrite phase transformation during the hot rolling cooling process. C also has a strong solid solution strengthening effect, which can improve the strength of the martensitic matrix and help to obtain a tensile strength of more than 1200MPa. In addition, C combines with Nb and Ti to form microalloy carbides, which precipitate on the tempered martensitic matrix, which can improve the yield strength and yield strength ratio, thereby improving the flanging and hole expansion performance of martensitic steel. In order to obtain the above beneficial effects, the C content cannot be less than 0.10%; at the same time, in order to avoid damaging the forming performance and welding performance, the upper limit of the C content is controlled at 0.25%. Exemplarily, the C content can be 0.1%, 0.12%, 0.15%, 0.18%, 0.20%, 0.22%, 0.25%, etc.

[0046] The positive effect of controlling the Si content to 0.1% to 0.5%: Si plays two roles in hot-rolled galvanized martensitic steel. One is to improve the hardness and strength of martensite through solid solution strengthening; the other is to inhibit the formation of cementite during annealing and galvanizing. However, when the Si content is too high, it will promote the formation of ferrite during the hot rolling process and deteriorate the surface quality of the hot-rolled plate. Therefore, the Si content is controlled at 0.1% to 0.5%. Exemplarily, the Si content is 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, etc.

[0047] The positive effect of controlling the Mn content to 1.5% to 2.5% is that Mn is an element that improves hardenability, can inhibit the formation of ferrite and bainite during hot rolling, and promote martensitic transformation. In addition, Mn is also an important strengthening element, which improves the strength of martensite through solid solution strengthening to ensure that a tensile strength of 1200MPa or more is obtained. However, when the Mn content is higher than 2.5%, it is easy to cause element segregation, resulting in uneven mechanical properties and decreased forming performance. Therefore, the present invention sets the Mn content range to 1.5% to 2.5%. Exemplarily, the Mn content can be 1.5%, 1.8%, 2.0%, 2.2%, 2.4%, 2.5%, etc.

[0048] The positive effect of controlling the P content to 0-0.01% is that as an interstitial solid solution atom, P can appropriately improve the strength of the steel plate, but it is also easy to segregate at the grain boundary and deteriorate the plasticity and formability, so the upper limit of the P content is set to 0.01%. For example, the P content can be 0, 0.001%, 0.002%, 0.004%, 0.006%, 0.008%, 0.01%, etc.

[0049] The positive effect of controlling the S content to 0-0.003% is that S is easy to combine with Mn to form coarse MnS inclusions, which deteriorates the forming properties of the steel plate such as hole expansion and flanging, so the upper limit of the S content is set to 0.003%. For example, the S content can be 0, 0.001%, 0.002%, 0.003%, etc.

[0050] The positive effect of controlling the Al content to 0.01% to 0.3% is as follows: In hot-rolled galvanized martensitic steel, the main function of Al is to inhibit the formation of cementite during annealing and galvanizing at 600°C to 660°C, but Al is also a ferrite-forming element. When the content exceeds 0.3%, it will accelerate the ferrite phase transformation during hot rolling, increase the critical cooling rate of the martensitic phase transformation, and increase the difficulty of hot rolling cooling. Taking all the above reasons into consideration, the present invention sets the Al content to between 0.01% and 0.3%. Exemplarily, the Al content can be 0.01%, 0.05%, 0.10%, 0.15%, 0.20%, 0.25%, 0.3%, etc.

[0051] The positive effect of controlling the Cu content to 0.05% to 0.5% is that the use of tempering to promote the precipitation of Cu-rich phase is a common strengthening method for Cu-containing low-alloy high-strength steel. The annealing temperature of the hot-rolled galvanized martensitic steel of the present invention is 600°C to 660°C, which is a suitable precipitation temperature range for the Cu-rich phase. Therefore, a certain amount of Cu element is added to improve the yield strength and yield strength ratio of the martensitic steel by using the precipitation of the Cu-rich phase during the annealing process. In addition, the Cu-rich phase can also serve as a hydrogen trap to improve the hydrogen embrittlement resistance of martensitic steel. However, Cu is a more expensive alloying element. In order to control costs, its content is limited to no more than 0.5%. Exemplarily, the Cu content can be 0.05%, 0.10%, 0.15%, 0.20%, 0.25%, 0.30%, 0.35%, 0.45%, 0.5%, etc.

[0052] The positive effect of controlling the Ni content to 0.02% to 0.2% is that in order to prevent the "copper brittleness" problem during the hot rolling of hot-rolled galvanized martensitic steel containing Cu, a certain amount of Ni element needs to be added to the steel. Usually, the mass fraction ratio of Ni to Cu is greater than one-third. At the same time, in order to avoid excessive Ni addition and increase costs, the upper limit of Ni is controlled to 0.2%. Exemplarily, the Ni content can be 0.02%, 0.05%, 0.08%, 0.10%, 0.15%, 0.18%, 0.2%, etc.

[0053] The positive effect of controlling the Nb content to 0-0.05% is that Nb not only has a significant grain refinement effect, but is also a strong carbide-forming element. It can improve the yield strength of martensitic steel through precipitation strengthening, which is beneficial to the improvement of local forming performance such as hole expansion and bending. However, Nb significantly inhibits recrystallization. Too high Nb content will cause hot rolling to enter the non-recrystallization zone, resulting in the formation of deformation bands along the rolling direction, resulting in uneven performance. Based on the above factors, the Nb content needs to be controlled below 0.05%. Exemplarily, the Nb content can be 0, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, etc.

[0054] The positive effect of controlling the Ti content to 0.02% to 0.1%: Like Nb, Ti is also a strong carbide-forming element, which can improve the yield strength through precipitation strengthening. At the same time, Ti is beneficial to grain refinement and obtaining a uniform equiaxed microstructure. In addition, the cost of Ti is lower than that of Nb. In order to obtain a good precipitation strengthening effect while avoiding saturation of the precipitation effect, the Ti content needs to be controlled between 0.02% and 0.1%. Exemplarily, the Ti content can be 0.02%, 0.03%, 0.05%, 0.06%, 0.08%, 0.09%, 0.1%, etc.

[0055] The positive effect of controlling the B content to 0.001% to 0.003% is that B has strong hardenability, which can delay the formation of ferrite and pearlite during the hot rolling cooling process and promote the martensitic phase transformation. When the B content exceeds 0.003%, "boron embrittlement" is likely to occur, so its content is controlled to 0.001% to 0.003%. For example, the B content can be 0.001%, 0.002%, 0.0025%, 0.003%, etc.

[0056] In some embodiments, the microstructure of the steel matrix includes, by area ratio, tempered martensite: 90% to 99%, and other structures: 1% to 10%, wherein the other structures include one or more of ferrite, bainite, and retained austenite.

[0057] The positive effect of controlling the area ratio of tempered martensite to 90% to 99% and the area ratio of one or more of ferrite, bainite and retained austenite to 1% to 10% is as follows: tempered martensite is the main component phase in hot-rolled galvanized martensitic steel. When the area fraction is lower than 90%, the tensile strength of 1200MPa and above cannot be obtained. In addition, based on the incompleteness of phase transformation, a certain amount of ferrite, bainite or retained austenite is allowed and must exist in martensitic steel, but the total amount cannot exceed 10%, otherwise it will lead to a decrease in tensile strength and local formability, and excessive residual austenite content will also increase the risk of delayed cracking. Exemplarily, the area ratio of tempered martensite can be 90%, 91%, 93%, 95%, 97%, 98%, 99%, etc.; the total area ratio of ferrite, bainite and residual austenite can be 1%, 2%, 5%, 8%, 10%, etc.; the total area ratio of ferrite and residual austenite can be 1%, 2%, 5%, 8%, 10%, etc.; the total area ratio of ferrite and bainite can be 1%, 2%, 5%, 8%, 10%, etc.; the total area ratio of bainite and residual austenite can be 1%, 2%, 5%, 8%, 10%, etc.; the area ratio of ferrite can be 1%, 2%, 5%, 8%, 10%, etc.; the area ratio of bainite can be 1%, 2%, 5%, 8%, 10%, etc.; the area ratio of residual austenite can be 1%, 2%, 5%, 8%, 10%, etc.

[0058] In some embodiments, a precipitate phase is distributed on the matrix of the tempered martensite, and the precipitate phase includes one or more of a Cu-rich phase, NbC, TiC, and (Nb, Ti)C.

[0059] In the embodiment of the present application, due to the softening effect of annealing and galvanizing, the strength of the hot-rolled martensitic matrix is ​​bound to decrease, so it is necessary to compensate for the strength loss by precipitation strengthening to ensure a tensile strength of 1200MPa. Based on the differences in alloy composition design, the precipitation on the tempered martensitic matrix should include at least one of Cu-rich phase, NbC, TiC and (Nb, Ti)C.

[0060] In some embodiments, the steel matrix satisfies at least one of the following properties: yield strength ≥950MPa, tensile strength ≥1200MPa, elongation after fracture ≥11%, hole expansion ratio ≥70%, and 180° ultimate cold bending radius r≤1.5a, where a is the thickness of the steel matrix.

[0061] In the embodiment of the present application, Cu, Nb and Ti are compositely strengthened. During the annealing and galvanizing process, Cu-rich phase, NbC, TiC or (Nb, Ti) C, etc. can be precipitated, which greatly improves the yield strength and yield strength ratio, improves the flanging and hole expansion performance, and the yield strength of the steel matrix can be 950MPa, 960MPa, 970MPa, 980MPa, 990MPa, 1000MPa, etc.; the tensile strength can be 1200M Pa, 1210MPa, 1220MPa, 1240MPa, 1260MPa, etc.; the elongation after fracture can be 11%, 11.2%, 11.5%, 11.8%, 12.0%, 12.2%, etc.; the hole expansion rate can be 70%, 71%, 72%, 74%, 75%, 76%, etc.; the 180° extreme cold bending radius r can be 1.1a, 1.2a, 1.3a, 1.4a, 1.5a, etc.

[0062] Figure 1 A schematic flow chart of a method for preparing 1200MPa grade hot-rolled galvanized martensitic steel provided in an embodiment of the present application.

[0063] See also Figure 1 The present application provides a method for preparing 1200MPa grade hot-rolled galvanized martensitic steel, the method comprising:

[0064] S1, obtaining a slab having the chemical composition;

[0065] In some embodiments, before the step S1, the process further includes obtaining molten steel for smelting and casting it into slabs by continuous casting;

[0066] S2, heating, rough rolling, fine descaling, fine rolling, cooling after rolling and coiling the slab to obtain a hot-rolled coil;

[0067] In some embodiments, the heating temperature is 1240° C. to 1270° C., and the soaking time is 30 min to 50 min; and / or,

[0068] The end temperature of the rough rolling is 1070°C to 1140°C; and / or,

[0069] The inlet temperature of the finishing rolling is 1000°C to 1050°C, and the final rolling temperature is 860°C to 900°C; and / or,

[0070] The coiling temperature is 300°C to 400°C.

[0071] In the embodiment of the present application, the positive effect of controlling the heating temperature of the slab to be 1240°C to 1270°C is that when the heating temperature is lower than 1240°C, the alloy elements are not fully dissolved; when the heating temperature is higher than 1270°C, it is easy to cause coarse grains and surface decarburization. Exemplarily, the heating temperature of the slab can be 1240°C, 1250°C, 1260°C, 1270°C, etc.

[0072] The positive effect of controlling the soaking time to 30 minutes to 50 minutes is that when the soaking time is less than 30 minutes, the alloy elements are not fully dissolved; when the soaking time is more than 50 minutes, the iron oxide scale on the surface of the ingot becomes thicker. For example, the soaking time is 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, etc.

[0073] The positive effects of controlling the rough rolling end temperature to 1070℃~1140℃: When the rough rolling end temperature is lower than 1070℃, the descaling effect at the finishing entrance is poor and the deformation resistance in the finishing stage increases; when the rough rolling end temperature is higher than 1140℃, the overall temperature in the finishing stage is too high, and the grain growth rate after dynamic recrystallization increases, which is not conducive to grain refinement. Exemplarily, the rough rolling end temperature is 1070℃, 1080℃, 1090℃, 1100℃, 1110℃, 1120℃, 1130℃, 1140℃, etc.

[0074] The positive effects of controlling the finishing rolling entrance temperature to 1000℃~1050℃: When the finishing rolling entrance temperature is lower than 1000℃, the rolling deformation resistance increases, and the edge temperature drop increases, which is easy to cause the difference in the microstructure and performance between the edge and the middle; when the finishing rolling entrance temperature is higher than 1050℃, it is not conducive to the grain refinement in the finishing rolling stage. Exemplarily, the finishing rolling entrance temperature is 1000℃, 1010℃, 1020℃, 1030℃, 1040℃, 1050℃, etc.

[0075] The positive effects of controlling the final rolling temperature to 860℃~900℃: When the final rolling temperature is lower than 860℃, the rolling enters the non-recrystallization zone, resulting in obvious banded structure and reduced uniformity of mechanical properties; when the final rolling temperature is higher than 900℃, the austenite and martensite grains after phase transformation are relatively large, reducing the tensile strength, and high temperature final rolling is not conducive to the control of the cooling terminal temperature of the thin steel plate. Exemplarily, the final rolling temperature is 860℃, 870℃, 880℃, 890℃, 900℃, etc.

[0076] The positive effects of controlling the coiling temperature to 300℃~400℃: when the coiling temperature is lower than 300℃, the coiler load increases, which may easily lead to coiling tower and stacking faults; when the coiling temperature is higher than 400℃, the bainite ratio increases and the tensile strength decreases. Exemplarily, the coiling temperature is 300℃, 310℃, 320℃, 340℃, 350℃, 360℃, 380℃, 390℃, 400℃, etc.

[0077] In some embodiments, the thickness of the hot-rolled coil and the pressure of the finish descaling satisfy the following relationship:

[0078] When the thickness of the hot-rolled coil is 1.8 mm ≤ d ≤ 2.5 mm, the pressure of the finish descaling is 21 MPa to 24 MPa, where d is the thickness of the hot-rolled coil;

[0079] When the thickness of the hot-rolled coil is 2.5 mm < d ≤ 3.5 mm, the pressure of the finish descaling is 24 MPa to 27 MPa, where d is the thickness of the hot-rolled coil;

[0080] When the thickness of the hot-rolled coil is 3.5 mm < d ≤ 6.0 mm, the pressure of the finish descaling is 27 MPa to 30 MPa, where d is the thickness of the hot-rolled coil.

[0081] When controlling the thickness of the hot-rolled coil to be greater than or equal to 1.8 mm and less than or equal to 2.5 mm, the finish descaling pressure is 21 MPa to 24 MPa; when the thickness of the hot-rolled coil is greater than 2.5 mm and less than or equal to 3.5 mm, the finish descaling pressure is 24 MPa to 27 MPa; when the thickness of the hot-rolled coil is greater than 3.5 mm and less than or equal to 6.0 mm, the finish descaling pressure is 27 MPa to 30 MPa. The positive effects are as follows: Increasing the finish descaling pressure is to better remove the scale on the surface of the intermediate billet. However, for thin-gauge steel plates, too high a finish descaling pressure will cause sudden changes in the plate shape. Therefore, the above-mentioned descaling pressure design principle is determined based on the thickness specification. Exemplarily, when the thickness of the hot-rolled coil is 1.8 mm, 1.9 mm, 2.0 mm, 2.1 mm, 2.2 mm, 2.3 mm, 2.4 mm, 2.5 mm, etc., the finish descaling pressure can be 21 MPa, 22 MPa, 23 MPa, 23.5 MPa, 24 MPa, etc.; when the thickness of the hot-rolled coil is 2.6 mm, 2.7 mm, 2.8 mm, 3.0 mm, 3.2 mm, 3.4 mm, 3.5 mm, etc., the finish descaling pressure can be 24 MPa, 25 MPa, 26 MPa, 27 MPa, etc.; when the thickness of the hot-rolled coil is 3.6 mm, 4.0 mm, 4.5 mm, 5.0 mm, 5.5 mm, 5.8 mm, 6.0 mm, etc., the finish descaling pressure can be 27 MPa, 28 MPa, 29 MPa, 30 MPa, etc.

[0082] In some embodiments, the instantaneous minimum cooling rate of post-rolling cooling ≥ 25 °C / s, and the average cooling rate ≥ 30 °C / s; the thickness of the hot-rolled coil and the cooling method of post-rolling cooling satisfy the following relationship:

[0083] When the thickness of the hot-rolled coil is 1.8 mm ≤ d ≤ 3.5 mm, laminar water cooling is adopted for post-rolling cooling, where d is the thickness of the hot-rolled coil.

[0084] When the thickness of the hot-rolled coil is 3.5 mm < d ≤ 6.0 mm, combined water cooling of ultra-fast cooling and laminar water cooling is adopted for post-rolling cooling, where d is the thickness of the hot-rolled coil.

[0085] Positive effects of controlling the instantaneous minimum cooling rate ≥ 25 °C / s and the average cooling rate ≥ 30 °C / s during the controlled cooling process: When the instantaneous minimum cooling rate is lower than 25 °C / s, it will be lower than the theoretical critical cooling rate for all austenite to transform into martensite, resulting in uncontrollable formation of part of ferrite and bainite, which is not conducive to the improvement of the overall strength of martensitic steel; when the average cooling rate is lower than 30 °C / s, it cannot be accurately cooled to the set coiling temperature within the normal rolling speed range, and it will also lead to the formation of part of non-martensitic structure. Exemplarily, the instantaneous minimum cooling rate of this post-rolling cooling can be 25 °C / s, 26 °C / s, 27 °C / s, 28 °C / s, 29 °C / s, 30 °C / s, etc.; the average cooling rate can be 30 °C / s, 31 °C / s, 33 °C / s, 35 °C / s, 37 °C / s, 40 °C / s, etc.

[0086] S3. Perform surface treatment on the hot-rolled coil to obtain a pickled sheet; and

[0087] In some embodiments, the surface treatment includes descaling and temper rolling and continuous pickling. The elongation of the descaling and temper rolling is 0.3% - 0.5%; the strip running speed of the continuous pickling is 80 m / min - 180 m / min, and the free acid concentration in the pickling tank is 20 g / L - 30 g / L.

[0088] Positive effects of controlling the pickling speed to be 80 m / min - 180 m / min: When the pickling speed is lower than 80 m / min, the strip stays in the pickling tank for too long, which is likely to cause over-pickling of the grain boundaries on the surface layer, forming micro-grooves, and zinc flow mark defects are likely to occur after galvanizing; when the pickling speed is higher than 180 m / min, the removal effect of the scale / red rust on the strip surface is not good. Exemplarily, the strip running speed of this continuous pickling can be 80 m / min, 90 m / min, 100 m / min, 120 m / min, 140 m / min, 160 m / min, 180 m / min, etc.

[0089] Positive effects of controlling the elongation of the descaling and temper rolling to be 0.3% - 0.5%: When the elongation is lower than 0.3%, the scale breaking effect is not good; when the elongation is higher than 0.5%, the surface scale is overly broken, which is likely to cause over-pickling. Exemplarily, the elongation of the descaling and temper rolling can be 0.3%, 0.35%, 0.40%, 0.45%, 0.5%, etc.

[0090] The positive effect of controlling the free acid concentration to 20g / L to 30g / L: When the free acid concentration of the pickling tank is lower than 20g / L, the removal effect of iron oxide scale is poor; when the free acid concentration is higher than 30g / L, it is easy to cause over-pickling of the strip surface, which ultimately affects the surface quality of galvanizing. For example, the free acid concentration of the pickling tank can be 20g / L, 22g / L, 24g / L, 26g / L, 28g / L, 30g / L, etc.

[0091] S4, performing continuous annealing and galvanizing on the pickled plate, and then cooling to room temperature to obtain hot-rolled galvanized martensitic steel.

[0092] In some embodiments, the pickled plate is subjected to continuous annealing and galvanizing, and then cooled to room temperature to obtain hot-rolled galvanized martensitic steel, comprising:

[0093] Preheating the pickling plate to 210°C to 230°C;

[0094] The preheated pickling plate is heated to 600°C to 660°C at a rate of 5°C / s to 25°C / s;

[0095] Keeping the heated pickled plate warm for 30s to 80s;

[0096] The pickled plate after heat preservation is rapidly cooled to 420°C to 440°C at a rate of 5°C / s to 15°C / s;

[0097] The pickled steel sheet after rapid cooling is galvanized, and the thickness of the galvanized layer is controlled to be 7 μm to 20 μm, so as to obtain a galvanized steel sheet;

[0098] Cooling the galvanized steel sheet to 220° C. to 250° C.;

[0099] The cooled galvanized steel sheet is subjected to skin-pass treatment, and the skin-pass rolling force is controlled to be 1500 kN to 2500 kN, and then cooled to room temperature to obtain hot-rolled galvanized martensitic steel.

[0100] The positive effects of controlling the heating rate to 5℃ / s to 25℃ / s: When the heating rate is lower than 5℃ / s, the strip steel stays in the continuous annealing furnace for a long time, which may cause excessive tempering or even decomposition of martensite; when the heating rate is too fast and higher than 25℃ / s, it may cause the surface temperature of thick-gauge strip steel to be high while the core temperature to be low, i.e., a temperature difference may occur, which is not conducive to the regulation of organizational properties. For example, the heating rate of the heating section may be 5℃ / s, 10℃ / s, 15℃ / s, 20℃ / s, 23℃ / s, 25℃ / s, etc.

[0101] The positive effects of controlling the soaking temperature to 600℃~660℃: When the soaking temperature is lower than 600℃, the redox property of the strip surface is poor, resulting in weak chemical reaction between the plating solution and the steel plate surface, and the appearance of surface zinc flow lines, dezincification and other defects; when the soaking temperature is higher than 660℃, the hot-rolled martensite is over-tempered, resulting in a significant decrease in tensile strength, and the 1200MPa tensile strength cannot be guaranteed. Exemplarily, the soaking temperature can be 600℃, 610℃, 620℃, 630℃, 640℃, 650℃, 660℃, etc.

[0102] The positive effect of controlling the soaking time to 30s to 80s: When the soaking time is less than 30s, the precipitation phases of Cu, Nb and Ti are not fully precipitated during the soaking stage, and the yield strength and yield strength ratio cannot be effectively improved; when the soaking time exceeds 80s, the martensite is over-tempered, and it is difficult to ensure a tensile strength of more than 1200MPa. Exemplarily, the soaking time is 30s, 40s, 50s, 60s, 70s, 80s, etc.

[0103] The positive effects of controlling the rapid cooling rate to 5℃ / s to 15℃ / s: When the rapid cooling rate is lower than 5℃ / s, the strip steel stays in the high temperature zone of the continuous annealing furnace for a relatively long time, which aggravates the martensite tempering; when the rapid cooling rate is higher than 15℃ / s, it is difficult to control the cooling end temperature of the strip steel, and the large fluctuation of the temperature entering the pot is easy to cause zinc flow lines on the surface. Exemplarily, the rapid cooling rate of the cooling section can be 5℃ / s, 7℃ / s, 9℃ / s, 10℃ / s, 12℃ / s, 13℃ / s, 14℃ / s, 15℃ / s, etc.

[0104] The positive effects of controlling the temperature of the steel strip entering the pot to be 420℃~440℃: when the temperature of entering the pot is lower than 420℃, the chemical reaction between the zinc liquid and the surface of the steel strip becomes weaker, which may lead to poor adhesion of the coating; when the temperature of entering the pot is higher than 440℃, the solidification speed of the zinc liquid on the surface of the steel strip after the steel strip is taken out of the pot becomes slower, which may easily form zinc flow lines. For example, the temperature of the steel strip entering the pot may be 420℃, 425℃, 430℃, 435℃, 438℃, 440℃, etc.

[0105] The positive effects of controlling the skin-pass rolling force to be 1500kN to 2500kN are: when the skin-pass rolling force is lower than 1500kN, the coating surface is rough; when the skin-pass rolling force is higher than 2500kN, thin-gauge strip steel is prone to skin-pass wavy shapes. For example, the skin-pass rolling force can be 1500kN, 1700kN, 1900kN, 2100kN, 2300kN, 2500kN, etc.

[0106] In some embodiments, the zinc liquid composition of the continuous annealing galvanizing includes, by mass fraction: Al: 5% to 8%, Mg: 1.5% to 4%, and the remainder is Zn and unavoidable impurities.

[0107] The product prepared by the method for preparing 1200MPa grade hot-rolled galvanized martensitic steel is the above-mentioned 1200MPa grade hot-rolled galvanized martensitic steel. The chemical composition and microstructure of the 1200MPa grade hot-rolled galvanized martensitic steel prepared by the method for preparing 1200MPa grade hot-rolled galvanized martensitic steel can refer to the above-mentioned embodiment. Since the method for preparing 1200MPa grade hot-rolled galvanized martensitic steel adopts part or all of the technical solutions of the 1200MPa grade hot-rolled galvanized martensitic steel embodiment, it has at least all the beneficial effects brought by the technical solutions of the 1200MPa grade hot-rolled galvanized martensitic steel embodiment, which will not be repeated here one by one.

[0108] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to industry standards. If there is no corresponding industry standard, then the conditions recommended by the manufacturer are followed.

[0109] (1) Molten steel of Examples 1-7 and Comparative Examples 1-4 was prepared and cast into slabs. The chemical compositions of the slabs are shown in Table 1.

[0110] Table 1 Chemical composition mass percentage of each embodiment and comparative example

[0111] Group C Si Mn Al Cu Ni Nb Ti B P S Example 1 0.16 0.3 2.0 0.03 0.2 0.08 - 0.08 0.0015 0.008 0.0005 Example 2 0.1 0.4 2.3 0.05 0.5 0.2 0.03 0.04 0.003 0.009 0.001 Example 3 0.13 0.25 2.5 0.1 0.3 0.15 0.04 0.02 0.0015 0.008 0.0008 Example 4 0.17 0.2 2.1 0.15 0.05 0.02 0.05 0.05 0.002 0.006 0.0006 Example 5 0.19 0.1 1.9 0.3 0.1 0.05 0.02 0.1 0.002 0.007 0.0005 Example 6 0.22 0.3 1.7 0.04 0.4 0.15 0.04 0.06 0.0015 0.008 0.0006 Example 7 0.25 0.5 1.5 0.2 0.4 0.2 0.05 0.08 0.003 0.008 0.001 Comparative Example 1 0.05 0.2 1.9 0.03 0.2 0.08 0.02 0.08 0.0015 0.006 0.0009 Comparative Example 2 0.14 0.1 2.0 0.05 0.3 0.1 0.03 0.05 0.0015 0.008 0.0007 Comparative Example 3 0.16 0.2 1.8 0.05 0.4 0.2 0.04 0.04 0.002 0.007 0.0008 Comparative Example 4 0.18 0.3 1.85 0.1 0.2 0.1 - 0.1 0.0015 0.006 0.001

[0112] (2) The slab is heated, and rough rolling, fine descaling, fine rolling, post-rolling cooling and coiling are performed in sequence to obtain a hot-rolled coil with a thickness of 1.8 mm to 6.0 mm. The slab heating temperature is 1240°C to 1270°C, the furnace soaking time is 30 min to 50 min, the rough rolling end temperature is 1070°C to 1140°C, the fine rolling inlet temperature is 1000°C to 1050°C, the final rolling temperature is 860°C to 900°C, and the coiling temperature is 300°C to 400°C. When the thickness of the hot-rolled coil is greater than or equal to 1.8 mm and less than or equal to 2.5 mm, the fine descaling pressure is 21 MPa to 24 MPa; when the thickness of the hot-rolled coil is greater than 2.5 mm and less than or equal to 3.5 mm, the fine descaling pressure is 24 MPa to 27 MPa; when the thickness of the hot-rolled coil is greater than 3.5 mm and less than or equal to 6.0 mm, the fine descaling pressure is 27 MPa to 30 MPa. When the thickness of the hot-rolled coil is greater than or equal to 1.8mm and less than or equal to 3.5mm, laminar water cooling is used for post-rolling cooling; when the thickness of the hot-rolled coil is greater than 3.5mm and less than or equal to 6.0mm, ultra-fast cooling + laminar water cooling is used for post-rolling cooling; the instantaneous minimum cooling rate during the cooling process is ≥25℃ / s, and the average cooling rate is ≥30℃ / s.

[0113] (3) The hot rolled coil is unrolled and the scale is removed by continuous pickling to obtain a pickled plate. The pickling process strip running speed is 80m / min to 180m / min, the scale breaking and straightening elongation before pickling is 0.3% to 0.5%, and the free acid concentration of the pickling tank is 20g / L to 30g / L.

[0114] The specific process parameters of each embodiment and comparative example are shown in Table 2.

[0115] Table 2 Hot rolling and pickling process parameters of various embodiments and comparative examples

[0116]

[0117] (4) The pickled steel sheet is preheated to 210°C to 230°C, then heated to 600°C to 660°C at a rate of 5°C / s to 25°C / s, soaked for 30s to 80s, and then cooled to 420°C to 440°C at a rate of 5°C / s to 15°C / s, and then galvanized in a zinc pot. After the steel strip exits the zinc pot, an air knife is used to control the zinc layer thickness to 7μm to 20μm, and then the steel strip is cooled to a tower top temperature of 220°C to 250°C by a mobile bellows. Finally, the skin-passing mill is used to control the skin-passing rolling force to 1500kN to 2500kN, thereby obtaining a hot-rolled galvanized martensitic steel.

[0118] The continuous hot-dip galvanizing process parameters of each embodiment and comparative example are shown in Table 3.

[0119] Table 3 Continuous hot-dip galvanizing process parameters of each embodiment and comparative example

[0120]

[0121]

[0122] The microstructure of hot-rolled galvanized martensitic steel was analyzed by metallographic microscope, Zeiss Ultra-55 scanning electron microscope and X-ray diffraction analyzer (XRD). The yield strength, tensile strength and elongation after fracture of martensitic steel were tested by ZWICK / Roell Z100 tensile testing machine, the hole expansion rate was tested by ZWICK BUP1000 forming testing machine, and the limit cold bending radius of martensitic steel was determined by microcomputer-controlled electro-hydraulic servo bending testing machine.

[0123] The microstructure and mechanical properties of each embodiment and comparative example are shown in Table 4.

[0124] Table 4 Microstructure and mechanical properties of each embodiment and comparative example

[0125]

[0126] Attached Figure 1It shows that more than 90% of the area fraction in the microstructure of the 1200MPa grade hot-rolled galvanized martensitic steel of the present invention is tempered martensite; Table 4 shows that the hot-rolled galvanized martensitic steel of the present invention has a yield strength of ≥950MPa, a tensile strength of ≥1200MPa, an elongation after fracture of ≥11%, a hole expansion rate of ≥70%, and a 180° limit cold bending radius r≤1.5a (a is the thickness of the strip).

[0127] In Comparative Example 1, the mass fraction of C is not within the range of the embodiments of the present invention, and the yield strength of the obtained martensitic steel is only 855 MPa, the tensile strength is only 1095 MPa, and the hole expansion rate is only 65%;

[0128] In Comparative Example 2, the coiling temperature is not within the range of the embodiment of the present invention, and the tensile strength of the obtained martensitic steel is only 1180 MPa;

[0129] In Comparative Example 3, the average cooling rate of hot rolling is not within the range of the embodiments of the present invention, the yield strength of the obtained martensitic steel is only 845MPa, the tensile strength is only 1085MPa, the hole expansion rate is only 48%, and the limit cold bending radius r>1.5a, which does not meet the requirements;

[0130] In Comparative Example 4, the soaking temperature is not within the range of the embodiments of the present invention, and the yield strength of the obtained martensitic steel is only 885 MPa, and the tensile strength is only 1065 MPa.

[0131] In addition, one or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:

[0132] (1) In the embodiment of the present invention, a 1200MPa grade hot-rolled galvanized martensitic steel is provided. Compared with cold-rolled martensitic steel of the same strength level, it has a low dependence on production line equipment and does not require a large amount of precious alloy elements such as Cr and Mo to improve hardenability, and the alloy cost is low.

[0133] (2) In an embodiment of the present invention, a 1200MPa grade hot-rolled galvanized martensitic steel is provided, which is compositely strengthened by Cu, Nb and Ti. During the annealing and galvanizing process at 600°C to 660°C, Cu-rich phase, NbC, TiC or (Nb, Ti)C, etc. can be precipitated, which can not only improve the yield strength and yield strength ratio, improve the flanging and hole expansion performance, but also serve as a hydrogen trap to improve the hydrogen embrittlement resistance of the martensitic steel.

[0134] (3) In an embodiment of the present invention, a method for preparing a 1200MPa grade hot-rolled galvanized martensitic steel is provided, which greatly improves the surface quality and corrosion resistance of conventional hot-rolled martensitic steel by comprehensively regulating parameters such as hot-rolling fine descaling, pickling speed, and acid concentration, and performing surface galvanizing treatment.

[0135] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A 1200MPa grade hot-rolled galvanized martensitic steel, characterized in that: The hot-rolled galvanized martensitic steel comprises a steel matrix and a galvanized layer attached to at least a part of the surface of the steel matrix. By mass fraction, the chemical composition of the steel matrix comprises: C: 0.1% - 0.25%, Si: 0.1% - 0.5%, Mn: 1.5% - 2.5%, P: 0 - 0.01%, S: 0 - 0.003%, Al: 0.01% - 0.3%, Cu: 0.05% - 0.5%, Ni: 0.02% - 0.2%, Nb: 0 - 0.05%, Ti: 0.02% - 0.1%, B: 0.001% - 0.003%, and the balance is Fe and unavoidable impurities.

2. The hot-rolled galvanized martensitic steel according to claim 1, characterized in that: By area ratio, the microstructure of the steel matrix comprises: tempered martensite: 90% - 99%, and the remaining microstructure: 1% - 10%. The remaining microstructure includes one or more of ferrite, bainite, and retained austenite.

3. The hot-rolled galvanized martensitic steel according to claim 2, characterized in that: Precipitates are distributed on the matrix of the tempered martensite. The precipitates include one or more of Cu-rich phase, NbC, TiC, and (Nb,Ti)C.

4. The hot-rolled galvanized martensitic steel according to claim 1, characterized in that: The steel matrix satisfies at least one of the following properties: yield strength ≥ 950 MPa, tensile strength ≥ 1200 MPa, elongation after fracture ≥ 11%, hole expansion rate ≥ 70%, 180° ultimate cold bending radius r ≤ 1.5a, where a is the thickness of the steel matrix.

5. A method for preparing the 1200MPa grade hot-rolled galvanized martensitic steel according to any one of claims 1 to 4, characterized in that: The method includes: obtaining a slab having the chemical composition; heating, rough rolling, finish descaling, finish rolling, post-rolling cooling, and coiling the slab to obtain a hot-rolled coil; performing surface treatment on the hot-rolled coil to obtain a pickled sheet; and performing continuous annealing and galvanizing on the pickled sheet and then cooling it to room temperature to obtain the hot-rolled galvanized martensitic steel.

6. The method according to claim 5, characterized in that The thickness of the hot-rolled coil and the pressure of the finish descaling satisfy the following relationship: If the thickness of the hot-rolled coil is 1.8 mm ≤ d ≤ 2.5 mm, then the pressure of the finish descaling is 21 MPa - 24 MPa, where d is the thickness of the hot-rolled coil; If the thickness of the hot-rolled coil is 2.5 mm < d ≤ 3.5 mm, then the pressure of the finish descaling is 24 MPa - 27 MPa, where d is the thickness of the hot-rolled coil; If the thickness of the hot-rolled coil is 3.5 mm < d ≤ 6.0 mm, then the pressure of the finish descaling is 27 MPa - 30 MPa, where d is the thickness of the hot-rolled coil.

7. The method according to claim 5, characterized in that The instantaneous minimum cooling rate of the post-rolling cooling ≥ 25 °C / s, and the average cooling rate ≥ 30 °C / s; the thickness of the hot-rolled coil and the cooling method of the post-rolling cooling satisfy the following relationship: If the thickness of the hot-rolled coil is 1.8 mm ≤ d ≤ 3.5 mm, then the post-rolling cooling adopts laminar flow water cooling, where d is the thickness of the hot-rolled coil; If the thickness of the hot-rolled coil is 3.5 mm < d ≤ 6.0 mm, then the post-rolling cooling adopts a combined water cooling of ultra-fast cooling and laminar flow water cooling, where d is the thickness of the hot-rolled coil.

8. The method according to claim 5, characterized in that The heating temperature is 1240 °C - 1270 °C, and the soaking time is 30 min - 50 min; and / or The finishing temperature of the rough rolling is 1070 °C - 1140 °C; and / or The inlet temperature of the finishing rolling is 1000°C to 1050°C, and the final rolling temperature is 860°C to 900°C; and / or, The coiling temperature is 300°C to 400°C.

9. The method according to claim 5, characterized in that The surface treatment includes: scale breaking and straightening and continuous pickling, the elongation of the scale breaking and straightening is 0.3% to 0.5%; the strip running speed of the continuous pickling is 80m / min to 180m / min, and the free acid concentration of the pickling tank is 20g / L to 30g / L.

10. The method according to claim 5, characterized in that The pickled plate is subjected to continuous annealing and galvanizing, and then cooled to room temperature to obtain hot-rolled galvanized martensitic steel, comprising: Preheating the pickling plate to 210°C to 230°C; The preheated pickling plate is heated to 600°C to 660°C at a rate of 5°C / s to 25°C / s; Keeping the heated pickled plate warm for 30s to 80s; The pickled plate after heat preservation is rapidly cooled to 420°C to 440°C at a rate of 5°C / s to 15°C / s; The pickled steel sheet after rapid cooling is galvanized, and the thickness of the galvanized layer is controlled to be 7 μm to 20 μm, so as to obtain a galvanized steel sheet; Cooling the galvanized steel sheet to 220° C. to 250° C.; The cooled galvanized steel sheet is subjected to skin-pass treatment, and the skin-pass rolling force is controlled to be 1500 kN to 2500 kN, and then cooled to room temperature to obtain hot-rolled galvanized martensitic steel.